Evaluating the Effectiveness of a Pilot-Scale Subsurface-Flow Constructed Wetland for Reducing Iron, Manganese, and Sulfate in Acid Mine Drainage from Former Coal Mining Areas - Zulfahmi Zulfahmi; Hendra Sani; Syamsuddin Syamsuddin (Jurnal IPTEK Bagi Masyarakat, 2026)
Acid mine drainage from former coal mining areas is characterized by low pH and elevated concentrations of dissolved metals and sulfate, which may degrade receiving-water quality and create long-term environmental risk. This study evaluated the effectiveness and applied relevance of a pilot-scale subsurface-flow constructed wetland in improving acid mine drainage quality by increasing pH and reducing iron, manganese, and sulfate. The novelty of the study lies in the integrated use of gravel, sand, limestone, organic support media, and wetland vegetation within a pilot unit designed for post-mining rehabilitation conditions, while assessing pH, Fe, Mn, and sulfate simultaneously as key indicators of treatment performance. A quasi-experimental pretest–posttest approach was used by comparing influent and effluent quality after treatment through the wetland media. The influent had a pH of 3.2, Fe of 12.50 mg/L, Mn of 8.20 mg/L, and sulfate of 420.00 mg/L. After treatment, the effluent pH increased to 6.1, while Fe decreased to 3.40 mg/L, Mn to 2.70 mg/L, and sulfate to 180.00 mg/L. The corresponding removal efficiencies were 72.80% for Fe, 67.07% for Mn, and 57.14% for sulfate. These findings indicate that pilot-scale subsurface-flow constructed wetlands can provide a simple, low-energy, and environmentally compatible option for post-mining water management and may support practical rehabilitation strategies where long-term chemical dosing is difficult to sustain.